Ethnoscience In Science Learning Research Trend: A Systematic Literature Review From 2013-2022 - Dimas Fahrudin; Sulistyo Saputro; Sarwanto (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to explore the development of ethnoscience research in science learning in the period of 2013-2022. The findings obtained are expected to become one of the reference maps for future ethnoscience research in science education. This research employed a systematic review. 151 documents were obtained in their correlation with ethnoscience in science education. The articles from Google Scholar and Scopus databases were collected using Publish or Perish (PoP) software and visualized with the support of the Vosviewer software application. The findings show that in science learning Ethnoscience Research in Science Education was widely published in the journal Physics Conferences, the learning model was dominated by the inquiry model, the research products were related to books, e-books and videos, learning materials were dominated by chemistry subject, while the research subjects were dominated by students at the elementary school and secondary school levels. The implementation of ethnoscience learning in science learning impacts the students’ critical and analytical thinking skills, science process skills, scientific literacy, conservation and environmental care attitudes, and good attitudes. Local wisdom implemented in science learning comes from a local culture interpreted ethically.